The effect of training methods on young female judo athletes - Hou, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: High intensity training is not only characteristic of specialized training, but also important in improving athletic ability. The manipulation of intensity plays a significant role in planning pre-competition training. An athlete`s training load and intensity are factors which can determine an athlete`s success. This research is designed to provide a reference for coaches in developing training by testing the heart rates and blood lactate in young female Judo athletes using different training methods. Methods This research tested athletes` heart rate and blood lactate after each match in a competition and tested their heart rate in exercise under match conditions and during special strength training courses. Heart rates of the athletes were recorded using Polar HR monitors during preparation activities, training and recovery. YSI-1500 Sport Lactate Analyzers were also used to test blood lactate. The results were compared with other trainees to evaluate the effect of different training methods. Results 1. The blood lactate of young female Judo athletes decreased 8.01±2.11mmol/L after competition in training. The average heart rate in competition was 160±9b/min, and maximal heart rate was 183±10b/ min. 2. There was a significant difference (P<0.05) between the heart rate of the young female Judo athletes after doing preparatory activity and formal activity. 3. The average heart rate in special strength training was 160±10 b/ min and the maximal heart rate was 171±11 b/ min. In exercise under match conditions the average was 159±10 b/ min and the maximal rate was 171±10 b/ min. Both of these results are lower than the heart rates for the more informal competition in training. Conclusions Greater effort should be made in training to arrange rivals and create an appropriate atmosphere so as to mimic real competition. Load intensity should be increased in preparatory activities to produce the desired effects and high intensity and efficient training programs should be developed to comply with the special requirements of high intensity activities in real competition.